Association of Food and General Parenting Practices with Young Children's Dietary Behaviors and the Role of Child Difficulty in Self-regulation (OR03-05-19). (13th June 2019) - Nguyen, Hoa; Frongillo, Edward; Blake, Christine; Shapiro, Cheri; Frith, Amy
Abstract: Objectives: Understand the association of food and general parenting practices with young children's dietary behaviors and the role of child difficulty in self-regulation in this relationship. Methods: Data were from the Early Childhood Longitudinal Study – Birth Cohort. Parent-child dyads with non-missing outcomes at age 5 (i.e., weekly frequency of intake of sugar-sweetened beverages, sweet foods and desserts, salty snack foods, fruits, and vegetables) were used (n = 3, 250 boys and 3, 150 girls). Analyses were done separately for boys and girls. Regression models with full information maximum likelihood were used accounting for clusters in Stata. Each outcome was regressed on food parenting variables at age 4 (i.e., rules about foods, and meal routines of eating as a family and at a regular time) and covariates. General parenting variables at age 4 (i.e., parent-child interaction, difficulty sticking with rules, harsh discipline, rules about watching television, and rules about bedtime), child difficulty in self-regulation at age 4, and their interactions were then added sequentially. Results: Better food parenting practices at age 4 were associated with less frequent intake of unhealthy and more frequent intake of healthy foods and beverages in both boys and girls at age 5, with some differences by gender. General parenting practices at age 4 were associated with dietary behaviors differently for boys and girls. Difficulty in self-regulation at age 4 significantly modified the association between parenting practices and child's dietary behaviors for boys (evening meals at a regular time and intake of sweet foods and desserts) and girls (parent-child interaction and intake of sugar-sweetened beverages; difficulty sticking with rules and intake of sweet foods and desserts; rules about foods and intake of fruits and vegetables; and harsh discipline and intake of fruits). Conclusions: Better food parenting and general parenting practices at age 4 were associated with children's healthy dietary behaviors at age 5. These associations differed by gender and child difficulty in self-regulation. Interventions to improve children's dietary behaviors should target parents and children to promote positive parenting in food and non-food settings and support children with difficulty in self-regulation. Funding Sources: None.